Vitamin D status of Canadians as measured in the 2007 to 2009 Canadian Health Measures Survey - Langlois, Kellie; Green-Finestone, Linda; Little, Julian; Hidiroglou, Nick; Whiting, Susan (Université d'Ottawa | University of Ottawa, 2010)
Background - Vitamin D deficiency is a global health problem, but little is known about the vitamin D status of Canadians. // Data and methods - The data are from the 2007 to 2009 Canadian Health Measures Survey, which collected blood samples. Descriptive statistics (frequencies, means) were used to estimate 25-hydroxyvitamin D [25(OH)D] concentrations among a sample of 5,306 individuals aged 6 to 79 years, representing 28.2 million Canadians from all regions, by age group, sex, racial background, month of blood collection, and frequency of milk consumption. The prevalence of deficiency and the percentages of the population meeting different cut-off concentrations were assessed. // Results - The mean concentration of 25(OH)D for the Canadian population aged 6 to 79 years was 67.7 nmol/L. The mean was lowest among men aged 20 to 39 years (60.7 nmol/L) and highest among boys aged 6 to 11 (76.8 nmol/L). Deficiency (less than 27.5 nmol/L) was detected in 4% of the population. However, 10% of Canadians had concentrations considered inadequate for bone health (less than 37.5 nmol/L) according to 1997 Institute of Medicine (IOM) Standards (currently under review). Concentrations measured in November-March were below those measured in April-October. White racial background and frequent milk consumption were significantly associated with higher concentrations. // Interpretation - As measured by plasma 25(OH)D, 4% of Canadians aged 6 to 79 years were vitamin D-deficient, according to 1997 IOM standards (currently under review). Based on these standards, 10% of the population had inadequate concentrations for bone health.
Keywords: ethnicity; milk; sun exposure